Mother of all shows [videorecording (DVD)] - Brock, Davis James; D'Agnostino, Melissa; D'agostino, Melissa; Malick, Wendie; Hinds, Darryl (Gravitas Ventures, 2024)
Follows Liza who retreats to a '70s variety show in her mind as she struggles to cope with the impending death of her mother, trying to work through parts of their past without losing herself in the process.